ANALISIS PEMASARAN KOPI ARABIKA ( Caffea arabica ) (Studikasus: Desa SitinjoII, Kecamatan Sitinjo, Kabupaten Dairi) - Ester Megawati Boang Manalu; Khairul Saleh; Faoeza Hafiz Saragih (Universitas Medan Area, 2019)
ABSTRACT Considering the importance of arabica coffee commodity for farmers, a clear picture of arabica coffee marketing channel from producer farmer to final consumer (Merchant) is needed so that the profit can be equally distributed. This study aims to determine the marketing channel, margin, marketing efficiency of arabica coffee in the village of Sitinjo II, Sitinjo Subdistrict, Dairi Regency. The method used is proportionate stratified random sampling as much as 50 farmers while collecting merchant samples taken by census method that is as much as 5 traders and for the factory is taken as many as 2 factories with Purposive sampling method. The results showed that there are two channels of arabica coffee marketing at the location of research that is, the first channel starts from the farmer to the factory in the village Sitinjo II Sitinjo District. The second channel starts from the farmers, the collecting merchant proceeds to the factory in the village of Sitinjo II, Sitinjo Subdistrict. The biggest marketing margin is RP.4.000 found on channel II and the more efficient channel is on channel I with an efficiency value of 7.51%.